Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/1061186x.2012.740674
|View full text |Cite
|
Sign up to set email alerts
|

Receptors, endocytosis, and trafficking: the biological basis of targeted delivery of antisense and siRNA oligonucleotides

Abstract: The problem of targeted delivery of antisense and siRNA oligonucleotides can be resolved into two distinct aspects. The first concerns devising ligand-oligonucleotide or ligand-carrier moieties that bind with high selectivity to receptors on the cell type of interest and that are efficiently internalized by endocytosis. The second concerns releasing oligonucleotides from pharmacologically inert endomembrane compartments so that they can access RNA in the cytosol or nucleus. In this review we will address both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 157 publications
(196 reference statements)
0
48
0
1
Order By: Relevance
“…A lot of data has been generated and discussed regarding this last and maybe most difficult hurdle [88,89]. It seems clear that the endocytosis pathway is dominating siRNA uptake, whether in naked or conjugated form, or in a delivery system.…”
Section: Cellular Uptake and Intracellular Traffickingmentioning
confidence: 98%
See 1 more Smart Citation
“…A lot of data has been generated and discussed regarding this last and maybe most difficult hurdle [88,89]. It seems clear that the endocytosis pathway is dominating siRNA uptake, whether in naked or conjugated form, or in a delivery system.…”
Section: Cellular Uptake and Intracellular Traffickingmentioning
confidence: 98%
“…Phagocytosis is restricted to specialized cells, such as macrophages, granulocytes and Kupffer cells. All these uptake mechanisms have been reviewed in depth elsewhere [89,94]. Although there are small, but important differences between these mechanisms, in nearly all cases of functional uptake, the siRNA agent ends up in an endosomal vesicle [89].…”
Section: Cellular Uptake and Intracellular Traffickingmentioning
confidence: 99%
“…Cell selective delivery through ligand conjugation depends on the binding affinity of the ligands to their receptors and the density of the receptors on the target cell surface [32]. Besides, the intrinsic uptake rate of the ONs also plays a role.…”
Section: Molecular Conjugatesmentioning
confidence: 99%
“…In recent years, a variety of chemical molecules have been covalently conjugated to siRNA to improve its stability, specificity and correspondence: Zhenjun Yang; Yun Wu state Key laboratory of Natural and Biomimetic Drugs, school ofDifferent siRNA conjugates possess their unique biological properties and characteristics, and cell-targeting peptides which specifically bind to overexpressed target proteins on the surface of certain cells can achieve specific endocytosis. 8 A common cell-targeting peptide is Arg-Gly-Asp peptide sequence (cRGD), which implement endocytosis by binding to overexpressed integrin αvβ3 receptors on tumor cell surface. 9 Many reports have demonstrated that the transport capacity of siRNAs was significantly improved when siRNAs were covalently conjugated with cRGD peptides.…”
Section: Introductionmentioning
confidence: 99%